European Trade Unions in the 21st Century
XXII, 319 p. 14 illus., 12 illus. in color.
Keywords: “This comprehensive and accessible volume provides a rich range of case studies of trade unions in Europe today, ranging across many ‘varieties of capitalism’ and identifying sources of trade union agency even at a time of huge political and structural challenges.” — Seán Ó Riain, Professor, National University of Ireland Maynooth “This volume makes a significant contribution to an important topic.” — Nils C. Bandelow, Professor, Technische Universität Braunschweig, Germany “A welcome and highly relevant contribution to the St Antony’s series.” —Kalypso Nicolaïdis, Professor, European University Institute, Italy Trade unions in Europe face a range of cross-cutting challenges. This includes the near-universal contraction in union membership; the related decline of traditionally highly unionised blue-collar industries; and the rise of automation, microprocessing, and digitalisation, which can make it cheaper for employers toinvest in machines than to pay humans to work. The breakdown of the standard contract of employment and increasing rates of precarious work have further transformed the world of work. Taken together, this makes any collectivist vision of society, and the notion of solidarity upon which trade unionism is built, difficult to sustain. All this raises tough questions for trade unionists, policy-makers, and researchers alike regarding the future of trade unions, the oldest and largest civil society movement in Europe. The contributions in this volume explore the prospects for union revival across a range of cases, including by focusing on the pursuit of legal remedies and on the opportunities associated with the network society to defend the interests of workers. This interdisciplinary volume includes contributions that consider the Czech Republic, Denmark, France, Finland, Germany, Spain, Sweden, Poland, the United Kingdom, and the EU level by researchers coming from a range of disciplines and backgrounds. The volume should especially appeal to researchers and practitioners working in the fields of political science, sociology, law, and business studies. Barry Colfer is Research Fellow in Politics at St Edmund’s College, University of Cambridge, UK and Max Weber Fellow at the European University Institute, Florence, Italy.